2003
DOI: 10.1021/jf030177n
|View full text |Cite
|
Sign up to set email alerts
|

Combined Impact of pH and Organic Acids on Iron Uptake by Caco-2 Cells

Abstract: Previous studies have shown that organic acids have an impact on both Fe(II) and Fe(III) uptake in Caco-2 cell. However, to what extent this effect is correlated with the anion of organic acids per se, or with the resulting decrease in pH, has not yet been clarified. Therefore, we studied the effect of five organic acids (tartaric, succinic, citric, oxalic, and propionic acid) on the absorption of Fe(II) and Fe(III) in Caco-2 cells and compared this with sample solutions without organic acids but set to equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…In contrast, following adjustment to pH 6.5 and digestion with pancreatin-bile, the dialysable iron concentration was reduced to 0.1 µmol L −1 and in this situation lactate further reduced the concentrations of dialysable iron, presumably by increasing the amount of iron complexed into particles larger than the molecular weight cut-off of the dialysis membrane while still being effectively soluble. The improved dialysability of iron, at pH 5.5, on addition of lactate may reflect competition between the phytate naturally present in the rye bread and the lactate, as previously suggested by Salovaara et al 27 The concentration of iron in the dialysates in these experiments is therefore more than two orders of magnitude less than those routinely used to study transport kinetics. 28,29 Therefore, saturation of key transporter activity is unlikely and the linear relationship between the concentration in the dialysate and uptake into the cell reported here would be predicted, particularly as phytate concentrations were standardised.…”
Section: Discussionsupporting
confidence: 62%
“…In contrast, following adjustment to pH 6.5 and digestion with pancreatin-bile, the dialysable iron concentration was reduced to 0.1 µmol L −1 and in this situation lactate further reduced the concentrations of dialysable iron, presumably by increasing the amount of iron complexed into particles larger than the molecular weight cut-off of the dialysis membrane while still being effectively soluble. The improved dialysability of iron, at pH 5.5, on addition of lactate may reflect competition between the phytate naturally present in the rye bread and the lactate, as previously suggested by Salovaara et al 27 The concentration of iron in the dialysates in these experiments is therefore more than two orders of magnitude less than those routinely used to study transport kinetics. 28,29 Therefore, saturation of key transporter activity is unlikely and the linear relationship between the concentration in the dialysate and uptake into the cell reported here would be predicted, particularly as phytate concentrations were standardised.…”
Section: Discussionsupporting
confidence: 62%
“…It should, however, be noted that phosphate also influences siderophore production and that iron is prone to form complexes with phosphate, which could have contributed to their findings. These in vivo results are nevertheless consistent with an in vitro study, which showed that lowering of the pH increased iron uptake (Salovaara et al ., ).…”
Section: Iron Speciation and Bacterial Iron Uptake Mechanisms In The mentioning
confidence: 97%
“…These results are consistent with the findings of Proulx et al (2007), who showed that maize fermentation or lactic acid addition can increase both iron solubility and bioavailability estimated using the Caco-2 cell model. The enhancing effect of organic acid on iron absorption has been attributed to two different mechanisms depending on the form of iron: the lower pH (for Fe 2+ and Fe 3+ ) and the chelation of Fe 3+ (Salovaara, Sandberg, & Andlid, 2003). Consequently, an acid matrix could help solubilise most of the iron and possibly even the contaminant iron.…”
Section: Iron Contamination and Bioaccessibilitymentioning
confidence: 99%